SUPPORTING EXAMINATION OF CT-SCAN ON POLYCYSTIC KIDNEY DISEASE PATIENT AT DUSTIRA HOSPITAL CIMAHI INDONESIA - Ilma Fiddiyanti; Hadi Alwani (Journal of Health and Dental Sciences, 2023)
Polycystic Kidney Disease (PKD) is the growth of many kidney cysts. PKD is divided into Autosomal Dominant Polycystic Kidney Disease (ADPKD) and Autosomal Recessive Polycystic Kidney Disease (ARPKD). ADPKD prevalence 1:500 and ARPKD 1:6000-40000. The patient, a 34-year-old male, came to the hospital with the main complaint of bilateral low back pain. Patients are given symptomatic treatment by diclofenac sodium 50mg 2 dd 1—supporting Examination for PKD diagnosis with CT-Scan. The author is interested in studying more about PKD because it is asymptomatic and only becomes symptomatic at the age of 30-40 years in ADPKD and has high mortality in the ARPKD type. DOI : 10.54052/jhds.v3n1.p99-114